Congenital Heart Malformations Masked by Infantile Gangliosidosis—Case Report and Growing Evidence for Metabolic Disease-Associated Aortopathies - Dana Elena Mîndru; Elena Țarcă; Elena Emanuela Braha; Alexandrina-Ștefania Curpăn; Solange Tamara Roșu; Dana-Teodora Anton-Păduraru; Heidrun Adumitrăchioaiei; Valentin Bernic; Ioana-Alexandra Pădureț; Alina Costina Luca (Diagnostics, 2024)
Gangliosidosis (ORPHA: 79255) is an autosomal recessive lysosomal storage disease (LSD) with a variable phenotype and an incidence of 1:200000 live births. The underlying genotype is comprised GLB1 mutations that lead to β-galactosidase deficiency and subsequently to the accumulation of monosialotetrahexosylganglioside (GM1) in the brain and other organs. In total, two diseases have been linked to this gene mutation: Morquio type B and Gangliosidosis. The most frequent clinical manifestations include dysmorphic facial features, nervous and skeletal systems abnormalities, hepatosplenomegaly, and cardiomyopathies. The correct diagnosis of GM1 is a challenge due to the overlapping clinical manifestation between this disease and others, especially in infants. Therefore, in the current study we present the case of a 3-month-old male infant, admitted with signs and symptoms of respiratory distress alongside rapid progressive heart failure, with minimal neurologic and skeletal abnormalities, but with cardiovascular structural malformations. The atypical clinical presentation raised great difficulties for our diagnostic team. Unfortunately, the diagnostic of GM1 was made postmortem based on the DBS test and we were able to correlate the genotype with the unusual phenotypic findings.